(3eeGQSGJ EOGQI GdehGQO GdHTQjIs (3ehLg Edi aGFOI WdHI SfI Chdi eGSJQ JNUU EOGQI ehGQO HTQjI s - (3HcGQ(B, (3BeGds ((3GdLRGFQs (3OGQ EjdjGA ddfTQ hGdJhRjYs, 2024)
(3eaghe GdGOGQI h GdhXGFa GdGOGQjI , GOGQI GdehGQO GdHTQjI , GdJWhQ GdJGQjNj dGOGQI GdehGQO GdHTQjI h JSejGJgG , JMdjd h JUeje h hUa h JhUja GdhXjaI , GdJhXja h GdJOQjH , GdGMJjGLGJ GdJOQjHjI , GdGLhQ h GdQhGJH , Jbjje GdGOGA , fXGe eYdheGJ GdehGQO GdHTQjI , GdSdGeh GdegfjI , GdMhGOK h GdGeQGV GdegfjI , WH GdYed , JSjjQ GdeSGQ Gdegfj h fXGe GdMhGaR , fXGe GdGfXHGW h GdMhGaR (B.s
Keywords: (3GOGQI GdGaQGOs; (3Gdbhi GdYGedIs